Non-ST-elevation myocardial infarction after complex percutaneous coronary intervention and transcatheter aortic valve implantation: a case report of bioprosthesis-related delayed coronary obstruction and its difficult diagnosis. Issue 5 (9th September 2020) - Rudziński, Piotr Nikodem; Mach, Markus; Gross, Christoph; Andreas, Martin
Abstract: Background: There is a high coincidence of significant coronary artery disease and severe aortic stenosis. Coronary revascularization should be performed prior to transcatheter aortic valve implantation (TAVI). We report a case of non-ST-elevation myocardial infarction (NSTEMI) after complex percutaneous coronary intervention (PCI) prior to TAVI, where differential diagnosis between coronary stent failure and bioprosthesis-related sinus obstruction was substantial. Case summary: A 79-year-old woman was re-admitted to the hospital 5 days after TAVI due to troponin-negative new-onset angina. She underwent complex PCI 3 days before TAVI and was not compliant to medications. Symptoms initially resolved after re-establishment of anti-hypertensive treatment. There were no signs of aortic bioprosthesis failure, paravalvular leak, or myocardial ischaemia. After 1 month, the symptoms re-occurred. Due to elevated troponins, myocardial ischaemia in electrocardiogram and new contractility disorders, NSTEMI was diagnosed. Because it was impossible to intubate the left coronary artery (LCA), cardiac surgery was performed. Calcified native coronary leaflet was pushed by the stent frame of aortic bioprosthesis towards LCA ostium causing its subtotal occlusion. Transcatheter heart valve (THV) was removed and the new surgical aortic bioprosthesis was implanted. Further hospitalization and 1-month follow-up were uneventful. Discussion: Pre-procedural assessment is crucial prior to THV interventions. Delayed coronary obstruction caused by the native leaflet is extremely rare and potentially fatal complication of TAVI. The diagnosis is difficult and high clinical suspicion is required to detect this pathology. Given our experience, the indication towards interventional or surgical repair should be established faster to avoid coronary ischaemia.